IMPACT OF BRITISH FOREST POLICIES ON JHOOM (NOMADIC)CULTIVATION AND THE PEOPLE OF UTTARAKHAND - Ms Anchal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With the establishment of British rule in India, economic and environmental changes began. But the most environmental changes took place in modern Uttarakhand because forests were needed for railway sleepers. The wood needed for railway sleepers could only be found in the hill forests of Uttarakhand. To get it, the British Indian government started controlling the hill forests of Uttarakhand, which started causing economic and environmental losses. Those who had been doing Jhum farming for centuries were banned. Due to the stoppage of Jhum farming, they adopted an animal husbandry business, but the British Indian government also banned their animals from grazing in the forest.